The Effect of Child Massage on Daytime Sleep Quality in Children Aged 2–3 Years - Ginanintha Amry Agustien; ⁠Indah Rahmaningtyas; Koekoeh Hardjito; Desy Dwi Cahyani (Jurnal Kebidanan Manna, 2026)
Background: Poor daytime sleep quality is commonly found among children aged 2–3 years and may adversely affect growth, development, and emotional regulation. One potential non-pharmacological intervention to improve sleep quality is kids massage. Objective: To analyze the effect of kids massage on daytime sleep quality among children aged 2–3 years at Permata and Al-Amiin Daycare Centers in Kediri City. Methods: This study employed a pre-experimental design using a one-group pretest-posttest approach. A total of 36 children were selected through simple random sampling. The intervention consisted of a 15-minute kids massage session conducted four times per week for two weeks. Daytime sleep quality was assessed using a questionnaire adapted from the Brief Infant Sleep Questionnaire-Revised (BISQ-R). Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of 0.05. Results: Before the intervention, only 11.1% of participants had good daytime sleep quality, increasing to 50.0% after the intervention. Meanwhile, the proportion of poor sleep quality decreased from 41.7% to 5.6%. The Wilcoxon test showed a Z value of -5.054 with a p-value < 0.001, indicating a statistically significant effect of kids massage on daytime sleep quality. Conclusion: Kids massage is effective in improving daytime sleep quality among children aged 2–3 years and can be recommended as a safe and practical non-pharmacological intervention for use at home and in daycare settings.